2019
DOI: 10.1002/cam4.2113
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting intratumoral myeloid cell plasticity by single cell RNA‐seq

Abstract: Tumor‐infiltrating myeloid cells are the most abundant leukocyte population within tumors. Molecular cues from the tumor microenvironment promote the differentiation of immature myeloid cells toward an immunosuppressive phenotype. However, the in situ dynamics of the transcriptional reprogramming underlying this process are poorly understood. Therefore, we applied single cell RNA‐seq (scRNA‐seq) to computationally investigate the cellular composition and transcriptional dynamics of tumor and adjacent normal ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 50 publications
2
105
0
Order By: Relevance
“…In addition, CD68 + cells without CD14 and SIRPα expression also displayed properties of Mo/MΦs and expressed other Mo/MΦ markers including CD16, CD32, and Lox-1. Previous studies have shown that Mo/MΦs commonly lose CD14 expression particularly when present in tumor tissue and other markers are utilized to define these subsets of Mo/MΦs 6,26,27 . Furthermore, SIRPα expression changes as MΦ become activated 28 , and we show in the present study that CD14 and SIRPα expression on intratumoral Mo/MΦs in FL allows for the definition of three distinct subgroups of cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CD68 + cells without CD14 and SIRPα expression also displayed properties of Mo/MΦs and expressed other Mo/MΦ markers including CD16, CD32, and Lox-1. Previous studies have shown that Mo/MΦs commonly lose CD14 expression particularly when present in tumor tissue and other markers are utilized to define these subsets of Mo/MΦs 6,26,27 . Furthermore, SIRPα expression changes as MΦ become activated 28 , and we show in the present study that CD14 and SIRPα expression on intratumoral Mo/MΦs in FL allows for the definition of three distinct subgroups of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on conditions that are likely to become cancers, such efforts are promising to unveil immune-based biomarkers in lung PMLs (e.g., by characterizing immune infiltrates) and to unravel potential immune interventional strategies at the earliest detectable stages of lung cancer. Resolving transcriptional and immune profiles at the single-cell level, for example of dissociated tumors, is now providing novel insights into intra-tumor heterogeneity, evolution, as well as the pre-existing immunity and its crosstalk with tumor initiation, progression, and response to immunotherapy (266,(271)(272)(273)(274). Future directions aimed at understanding the premalignant immune biology of various tumors promise to reveal unprecedented states of tumor plasticity, heterogeneity, and diversity of lymphoid and myeloid cell types in lesions, to harvest potential biomarkers for immunebased treatment of this fatal disease.…”
Section: Resultsmentioning
confidence: 99%
“…One study has showed the Mϕ with rheostatic phenotypes and M2 polarization in human lung tumor using scRNA‐seq to present 52,698 cell TME transcriptome . Similar study observed a highly positive correlation of M1 and M2 signature gene expressions in all the Mϕs through profiling immune landscape form 14 treatment naive TNBC tumors . The interaction among immune cell and other tissue cells holds the key for successful immunotherapy of tumors.…”
Section: Application Of Scrna‐seq In Immunologymentioning
confidence: 87%
“…The reprogramming of monocyte is known to be affected by the surrounding environment, such as tumors. Recently, an scRNA‐seq study tracked myeloid reprogramming between adjacent normal and tumor states and identified a differentiation path from CD14 + monocytes to M2 Mϕs using monocle2 trajectory analysis . Trajectory analyses are also used to examine the immune system development.…”
Section: Application Of Scrna‐seq In Immunologymentioning
confidence: 99%